Estimasi Sumber Daya Uranium Tipe Batupasir di Sektor Aloban, Sibolga, Tapanuli Tengah - Ciputra, Roni Cahya; Muhammad, Adi Gunawan; Adimedha, Tyto Baskara; Syaeful, Heri (EKSPLORIUM, 2019)
Uranium explorations in Sibolga Area have been conducted since 1978 by BATAN and successfully result in sandstone-type uranium mineralization. Research related to uranium mineralization concept on sandstone and conglomerate at Aloban Sector, Sibolga has been conducted through 22 boreholes data which resulted in the geological section, anomaly distribution along with radiometry counting and geochemistry data. This research objective is to obtain uranium resources in Aloban Sector by correlating radiometry counting and geochemical data from previous research by using a geostatistic approach. Geostatistical processing using SGeMS software shows a correlation coefficient of 0.5 so that the radiometry and geochemical data are interpreted to have a good correlation. Uranium Resources estimation was measured on Conglomerate I and Sandstone I units which are considered to have thick and wide mineralization distribution. The average uranium grade for Conglomerate I and Sandstone I units are 173.05 ppm U and 161.54 ppm U respectively. Uranium resource estimation at Aloban Sector is 415 tons as inferred resources.